Understanding the mechanisms of hydrolytic enzyme mediated organic matter decomposition under different land covers within a subtropical preserve - Melkani, Suraj; Manirakiza, Noel; Rabbany, Abul; Medina-Irizarry, Natalia; Smidt, Samuel; Braswell, Anna; Martens-Habbena, Willm; Bhadha, Jehangir H. (Frontiers in Environmental Science, 2025)
Soil Organic Matter (SOM) decomposition, vital to the carbon cycle, is influenced by land cover, hydrological conditions, and soil properties. However, understanding of how hydrolytic enzymes involved in SOM turnover vary under these factors remains limited. To address this, a study was conducted in a sub-tropical preserve in South Florida to assess hydrolytic enzyme activities across 23 diverse land covers (Categorized into five ecosystems: A-Upland Forests, B-Wetland ecosystems, C-Shrub ecosystems, D-Range Areas, and E-Barren ecosystems) during wet and dry seasons. The assessed enzymes were β-1,4 glucosidase (βG), β-1,4-N-acetyl glucosaminidase (β-NAG), Acid Phosphatase (AP), and Aryl Sulfatase (AS). A weighted index termed the Hydrolytic Enzyme Decomposition Indicator (HEDI) was derived using principal component analysis to summarize overall enzymatic activity as an indicator of decomposition. The results showed that among the land covers, βG, β-NAG, AP, and AS activities during the dry season ranged from 18.40 to 327.20, 14.71–351.90, 302.89–10,185.80, and 26.51–1,745.75 μg PNP/g soil/hr, respectively, while in the wet season, the activities for all enzymes except AS were higher, ranging from 4.08 to 398.66, 21.72–1,118.97, 372.38–11,960.36, and 28.26–1,475.09 μg PNP/g soil/hr. Among ecosystems, βG and β-NAG showed seasonal variability, with β-NAG consistently higher in A-Upland Forests, B-Range Areas, and C-Shrub. AP and AS showed minimal variation, with all enzymes showing lower activity in D-Barren ecosystems. HEDI values in the dry season A-Upland Forests exhibited the widest range (−0.962–1.613), indicating diverse decomposition rates, while Barren ecosystems showed consistently low activity (−0.928 to −0.916), suggesting lower decomposition. Correlation analysis revealed positive relationships between enzymatic activities and soil properties such as SOM (0.51–0.59), active carbon (0.46–0.58), soil protein (0.27–0.40), and cation exchange capacity (0.28–0.40), while bulk density showed negative correlations (−0.31 to −0.50). Overall, this study highlights the necessity of considering the complex interactions between soil properties, vegetation, moisture, and enzymatic activity in understanding SOM decomposition.